Evaluating and Enhancing Usability and Gamification in an SNBT Learning Application Based on ISO 9241-11: A Design Thinking Approach with Usability Testing and GAMEX - I Ketut Veda Suputra; Putu Yudia Pratiwi; I Made Ardwi Pradnyana (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2026)
This study evaluates and enhances the usability and gamification of Skuling, an Indonesian learning application built for SNBT preparation with gamified features, through a Design Thinking approach grounded in ISO 9241-11. Baseline usability testing was carried out with 16 participants through Performance Measurement, Retrospective Think-Aloud (RTA), and the GAMEX questionnaire across eight task scenarios, producing an average success rate of 69.92% and an error rate of 5.07%; while 6 tasks were considered Effective Enough, 2 were considered Ineffective. Thematic analysis of RTA data uncovered six recurring usability problems, the most severe being related to the Daily Missions and the friend-based search features. Findings were synthesized through the Empathize and Define stages, which were then translated into design solutions throughout the Ideate phase with the Eisenhower Matrix and Shneiderman’s Eight Golden Rules. Solutions were built into low-fidelity wireframes, an interactive Figma prototype, and a HTML/CSS & JavaScript front-end interface. Post-redesign testing with 6 of the initial 16 participants raised the average success rate to 93.75% and lowered the error rate to 1.11%, placing the redesign in the Highly Effective category. 4 out of 6 GAMEX dimensions reached the High category, with the lowest scoring dimension throughout both stages being Absorption, suggesting the construct may not suit high-stakes examination preparation contexts where users are meant to remain aware of time.